New Complex Analytic Methods in the Study of Non-Orientable Minimal Surfaces in ℝⁿ - Alarcón, Antonio; Forstnerič, Franc; López, Francisco J. (Memoirs of the American Mathematical Society, 2020)
The aim of this work is to adapt the complex analytic methods originating in modern Oka theory to the study of non-orientable conformal minimal surfaces in All our new tools mentioned above apply to non-orientable minimal surfaces endowed with a fixed choice of a conformal structure. This enables us to obtain significant new applications to the global theory of non-orientable minimal surfaces. In particular, we construct proper non-orientable conformal minimal surfaces in